Characteristicsx and suppression of NVH in twin screw refrigeration compressors. (August 2019) - Chen, W; Zhang, Z; He, Z; Xing, Z
Abstract: Characteristics of NVH (Noise, vibration and harshness) in twin screw refrigeration compressors, mainly caused by mechanical vibration and turbulent gas flow, are discussed in detail. According to the different generation mechanism, suppression methods of mechanical NVH and hydrodynamic NVH are proposed, respectively. Mechanical NVH is related to rotor profile, bearings, lubricating conditions and maching precision, while hydrodynamic NVH is inevitable and severe for all positive displacement compressors due to gas compression and turbulent flow. Concluded from three cases of NVH suppression for semi-hermetic twin screw refrigeration compressors, half-wave method based on acoustic interference theory, pulsation damper evolving from Helmholtz resonator and broadband perforated tube silencer are effective paths to alleviate hydrodynamic NVH in twin screw refrigeration compressors without bringing in extra energy losses.